Implementation of Nursing Care for Mrs. R in Craniotomy Tumor Removal with Brain Tumor Diagnosis - Pobela, Yusdianto; Alam, Rizqy Iftitah; Agustini, Tutik (PT.Mantaya Idea Batara, 2024)
Brain tumors are uncontrolled abnormal cells that continue to grow in the brain unconsciously, disrupting the brain's working system. Brain tumors have been divided into two large groups, namely primary and secondary or metastatic brain tumors. Both secondary brain tumors are tumors that originate from other parts of the body and then spread to the head (brain). This study aims to determine the application of nursing care for Mrs. R in the action of craniotomy removal of tumors with a diagnosis of brain tumors in the central surgical installation room of RSUD. Labuang Baji Makassar. This case study uses an observation method regarding the surgical procedure and is descriptive of the case study and nursing process approach. In this case study, the results were obtained after an assessment was carried out until nursing intervention was given for 1x5 hours. Then, the brain tumor was resolved by performing a craniotomy removal of the tumor. Based on the results of the discussion of the results of the case study and the nursing care provided, it can be concluded that the nursing diagnosis taken in the case of a brain tumor (meningioma) with a craniotomy removal of the tumor in the central surgical installation room of RSUD. Labuang Baji in the pre-phase is chronic pain and anxiety; in the intraoperative phase is the risk of bleeding; and in the postoperative phase is the risk of infection so that the nursing care actions given to the four diagnoses are in accordance with the interventions provided in the 3S book (SDKI, SLKI, SIKI).